Preparation technology of electrodeposited single-phase composition gradient nanocrystalline Fe-Co-Ni alloy
By performing DC plating on the substrate and adjusting the plating solution conditions, a nanocrystalline iron-cobalt-nickel alloy plating with component gradient is formed, which solves the problem of roughness and poor density of the electrodeposition method, and achieves hard plastic bonding and wear resistance Improvement.
Patent Information
- Application Number
- CN202211266050.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-17
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-10-17
AI Technical Summary
The iron-cobalt nickel alloy coating obtained by the existing electrodeposition method has rough surfaces, poor density, poor flatness, and poor bonding properties of hardness and plasticity.
By performing DC plating on the substrate, adding anionic surface brightener and wetting agent, the metal ion concentration and electrodeposition conditions in the plating solution are regulated, and nanocrystalline iron-cobalt-nickel alloy plating layer with component gradient is formed to achieve grain size and Gradient characteristics of hardness.
It forms a nanocrystalline iron-cobalt-nickel alloy coating with good surface brightness and density, with good hard plastic bonding and wear resistance, the crystal structure is FCC single-phase, and the grain size and hardness are gradiently distributed within a specific range.
Smart Images

Figure CN115449867B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of structural materials, and in particular relates to a method for forming a nanocrystalline iron-cobalt-nickel alloy coating having an FCC single phase and a composition gradient on a substrate by direct current electroplating. Background Art
[0002] Iron-cobalt-nickel alloys are widely used in aerospace, machinery manufacturing, electronics, metal material protection and other fields due to their excellent properties such as high strength, hardness, wear resistance, corrosion resistance and high temperature resistance. They have become an important material for surface coatings of some mechanical parts and metal equipment.
[0003] With the continuous development of science and technology, various industrial sectors have continuously improved the performance requirements of structural materials, especially metal materials, and the research on the manufacturing methods of excellent performance metal materials has become particularly important. Electrodeposition, also known as the electrocrystallization process (electroplating), refers to the process in which the cations in the plating solution move to the vicinity of the cathode under the action of an external current, obtain electrons and are deposited on the cathode substrate, thereby obtaining metal coatings of different thicknesses. Since the electrodeposition method can be used to manufacture bulk alloy coatings for structural performance research, and can also achieve surface treatment of materials by depositing thin film coatings on the surface of the material, and it is simple to operate and low in cost, it is an important method for manufacturing metal materials.
[0004] However, the current method of obtaining the iron-cobalt-nickel alloy coating by electrodeposition still has many disadvantages, such as rough coating surface, poor density, poor flatness, and the most critical poor combination of hardness and plasticity. Summary of the invention
[0005] The present invention provides a preparation process of a single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy by electrodeposition on a substrate. By adding various additives, many problems existing in the existing electrodeposition method, such as rough surface, poor density and poor flatness, are solved; and by regulating the metal ion concentration in the plating solution and various electrodeposition conditions, the plated alloy presents obvious composition gradient characteristics, thereby generating gradient grain size and gradient hardness, forming an alloy material with good hard-plastic bonding and wear resistance.
[0006] The invention provides a preparation process for electrodepositing a single-phase component gradient nanocrystalline iron-cobalt-nickel alloy on a substrate. The embodiment comprises the following steps: firstly, an initial plating solution containing nickel and iron ions is prepared, and the plating solution is subjected to impurity removal treatment to obtain a plating solution after impurities removal; the plating solution after impurities removal is added into an electroplating container, and an anionic surface brightener and a wetting agent are added; a soluble cobalt plate and a 304 stainless steel cathode plate material which have been subjected to surface treatment are placed into the plating solution, and direct current electroplating is performed for 12 hours to increase the concentration of cobalt ions in the plating solution, and decrease the concentrations of nickel ions and iron ions, and a pre-plating test is completed; in a formal electroplating test, the cathode material needs to be replaced with ductile iron, and the anode material needs to be replaced with a soluble nickel plate and an iron plate, and the current density is 1A / dm 2 , stirring speed is 80-120r / min, plating solution temperature is 70-80℃, and plating solution pH value is 2.0-2.5. Under this condition, DC electroplating is carried out for 7 days to deposit a nanocrystalline iron-cobalt-nickel alloy coating with a composition gradient on the surface of the cathode material.
[0007] The preparation process of the single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy electrodeposited on a substrate provided by the embodiment of the present invention adopts direct current electroplating to deposit a single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy coating on the surface of the surface-treated cathode plate material. The formed nickel-iron-cobalt alloy coating not only has a bright surface, good density, flatness and no cracks, but also has good hard-plastic bonding and wear resistance. The crystal structure of the alloy presents a single-phase structure of FCC, has an obvious composition gradient in the thickness direction of the coating, and thus produces a grain size gradient in the range of 20-40nm and a hardness gradient in the range of 4.6-5.6Gpa. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is the variation trend of the metal ion concentration in the plating solution configured by the method provided in the embodiment of the present invention, Figure 1 (a) and (b) are the changes of metal ion concentration in the plating solution with plating time in the pre-plating test and the formal electroplating test, respectively. Figure 1 (c) is the fitted relationship curve between the ion concentration of the coating and the ion concentration of the plating solution;
[0009] Figure 2 This is a surface SEM image of a gradient nanocrystalline iron-cobalt-nickel alloy prepared by the method provided in an embodiment of the present invention;
[0010] Figure 3 This is a cross-sectional SEM+EDS image of a gradient nanocrystalline iron-cobalt-nickel alloy prepared by the method provided in an embodiment of the present invention;
[0011] Figure 4 is a cross-sectional XRD diagram of a gradient nanocrystalline iron-cobalt-nickel alloy prepared by the method provided in an embodiment of the present invention;
[0012] Figure 5is a cross-sectional TEM image of a gradient nanocrystalline iron-cobalt-nickel alloy prepared by the method provided in an embodiment of the present invention, Figure 5 (a)-(d) are TEM images of four regions where the alloy is evenly distributed from the substrate side to the coating surface;
[0013] Figure 6 This is a cross-sectional hardness distribution diagram of a gradient nanocrystalline iron-cobalt-nickel alloy prepared by the method provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms of "a" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0015] The embodiment of the present invention provides a preparation process of electrodepositing a single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy on a substrate, which specifically includes the following steps:
[0016] Prepare an initial plating solution containing nickel and iron ions, and remove impurities from the plating solution to obtain a plating solution after impurities removal; add the plating solution after impurities removal into an electroplating container, and add anionic surface brightener and wetting agent; put the surface-treated soluble cobalt plate and 304 stainless steel cathode plate material into the plating solution, and perform DC electroplating for 12 hours to increase the concentration of cobalt ions in the plating solution and reduce the concentrations of nickel ions and iron ions, thus completing the pre-plating test; the formal electroplating test requires replacing the cathode material with ductile iron, and the anode material with soluble nickel plate and iron plate, with a current density of 1A / dm 2 , stirring speed is 80-120r / min, plating solution temperature is 70-80℃, and plating solution pH value is 2.0-2.5. Under this condition, DC electroplating is carried out for 7 days to deposit a nanocrystalline iron-cobalt-nickel alloy coating with a composition gradient on the surface of the cathode material.
[0017] In the embodiment of the present invention, the initial plating solution containing nickel-iron ions is prepared by the following steps:
[0018] Add a certain amount of deionized water into a cleaned beaker and heat it to 70-80°C. First weigh the required amount of boric acid and add it to the beaker. Heat and stir to dissolve it, and keep the solution in an acidic environment.
[0019] Weigh the required amounts of nickel sulfate, nickel chloride, sodium chloride and ferrous sulfate, add them into a beaker containing boric acid prepared in advance, heat and stir to dissolve them, and obtain a preliminary plating solution.
[0020] The concentrations of the components of the preliminary plating solution prepared above are: nickel sulfate 160-180 g / L, nickel chloride 45-55 g / L, sodium chloride 50-60 g / L, ferrous sulfate 40-60 g / L, and boric acid 50-60 g / L.
[0021] In the embodiment of the present invention, the plating solution is subjected to impurity removal treatment to remove insoluble or insoluble impurities in the plating solution, thereby improving the purity of the plating solution and thus improving the quality of the plating layer.
[0022] The step of removing impurities from the plating solution includes: adding activated carbon to the prepared preliminary plating solution, adsorbing it with magnetic stirring at 60-70°C for more than 4 hours, and then removing the activated carbon to obtain a plating solution with impurities removed.
[0023] Activated carbon is a black porous solid carbon with excellent adsorption capacity. It can adsorb insoluble or insoluble impurities in the plating solution, such as dust and fine sand mixed in when weighing medicines and insoluble small particles in the medicines.
[0024] In the embodiment of the present invention, the activated carbon in the plating solution is removed by a vacuum filter. The specific steps are as follows: the plating solution containing activated carbon is added to a filtration bottle, the filtration bottle is connected to a vacuum filter, and then three layers of filter paper are spread in the filter funnel, the filter paper is first wetted, and then the plating solution is slowly poured into the filtration bottle through the filter paper, and the filtration of the plating solution is repeated 3-4 times to obtain a plating solution after impurities are removed.
[0025] In the embodiment of the present invention, before the step of adding the impurity-removed plating solution into the electroplating container, adding anionic surface brightener and wetting agent, and placing the surface-treated anode plate and cathode plate materials into the electroplating container for electroplating, the process further includes:
[0026] After cutting, the soluble iron, cobalt and nickel plates are polished to remove the oxide layer on the surface; then ultrasonic cleaning is performed in alkaline cleaning solution and acid cleaning solution respectively to remove oil stains and impurities on the surface of the cathode plate to obtain the treated iron, cobalt and nickel plates.
[0027] The cathode plate material is placed in an alkaline cleaning solution at 70-80°C for ultrasonic cleaning for 20-30 minutes to remove oil stains and impurities on the surface of the cathode plate; the alkaline-washed cathode plate is placed in deionized water for ultrasonic cleaning for 2-3 minutes; and then placed in an acid cleaning solution for ultrasonic treatment for 20-30 seconds to remove the oxide layer on the surface of the cathode plate and activate the surface to obtain a treated cathode plate material.
[0028] In the embodiment of the present invention, the formula of the alkaline washing solution used is: 80g / L sodium hydroxide, 50g / L sodium carbonate, 30g / L sodium silicate, and 10g / L sodium phosphate; the acid washing solution is dilute sulfuric acid with a volume fraction of 10%.
[0029] In the embodiment of the present invention, the anode plate material is a soluble nickel, iron, and cobalt plate with a purity of more than 99.99%, and the sizes are 10cm×20cm, 10cm×10cm, and 10cm×10cm respectively; the cathode plate material is a 304 stainless steel plate and a ductile iron plate with a size of 10cm×10cm.
[0030] In the embodiment of the present invention, in the step of adding the impurity-removed plating solution into the electroplating container, and adding the anionic surface brightener and the wetting agent, the anionic surface brightener includes saccharin and 1,4-butynediol. The main function of saccharin is to inhibit grain growth and make the surface of the coating bright, while 1,4-butynediol can not only improve the brightness of the coating, but also greatly reduce the internal stress of the coating and avoid the generation of cracks in the coating. The wetting agent is sodium dodecyl sulfate, which can discharge the H2 adsorbed on the surface of the coating as soon as possible, thereby eliminating the possibility of pinholes in the coating and greatly improving the quality of the coating.
[0031] In the embodiment of the present invention, weighed saccharin and 1,4-butynediol are first added to the plating solution to fully dissolve them. The added concentrations are 5 g / L and 0.05 g / L, respectively.
[0032] In the embodiment of the present invention, sodium dodecyl sulfate is first mixed with a small amount of deionized water to form a paste, and then boiling deionized water is poured into the paste, and the paste is placed on an electric heating furnace and heated and stirred for 30 minutes to fully dissolve, and finally added to the plating solution and stirred and mixed evenly. The added concentration is 0.5 g / L.
[0033] Considering that the formal electroplating time is long, the plating solution needs to be continuously maintained during the plating process. ① The metal ion concentration in the plating solution needs to be regularly monitored during the plating process; ② Due to the presence of H in some parts of the plating solution, the plating solution is not completely maintained. + Consumption will also occur when it is reduced, and the pH of the plating solution will gradually increase. Therefore, it is necessary to continuously monitor and control the pH of the plating solution; ③ During the plating process, in order to avoid the continuous consumption of saccharin, the plating solution needs to be supplemented with saccharin. In addition, two solutions are prepared with deionized water to supplement the plating solution, namely a saccharin solution with a concentration of 5g / L and an acidic solution with a pH value of 1.2 (prepared with concentrated sulfuric acid).
[0034] Connect the above solution to the electroplating container with a catheter (to avoid backflow of the plating solution, do not insert the catheter into the plating solution), install a peristaltic pump in the middle of the catheter, plug the peristaltic pump into the time switch, and use the time switch to control the power on and off of the peristaltic pump. Adjust the power-on interval of the time switch connected to the acid solution to 30 minutes and the power-on time to 3 seconds; adjust the power-on interval of the time switch connected to the saccharin solution to 60 minutes and the power-on time to 3 seconds. The amount of saccharin added is 4.1×10 -4 mol / h.
[0035] In an embodiment of the present invention, a surface-treated cobalt plate and a 304 stainless steel cathode plate material are hung and fixed on two opposite inner surfaces of a plating tank, and DC electroplating is first performed for 12 hours to increase the concentration of cobalt ions in the plating solution and reduce the concentrations of nickel ions and iron ions, thereby completing a pre-plating test; then a ductile iron cathode plate material is replaced and fixed on a stirring rod with a copper wire instead of a stirring paddle, and then the cobalt plate is taken out and placed in a soluble nickel plate and an iron plate, and the cathode plate material is adjusted to the center of the plating solution and the distance from the nickel plate and the iron plate is almost the same (15-20 cm) to avoid uneven components of the alloy coating, and then the stirring motor is turned on for electroplating.
[0036] In the embodiment of the present invention, the thickness of the iron-cobalt-nickel alloy coating obtained by the above method is about 1200-1300 um.
[0037] The method for electroplating bulk nanocrystalline iron-cobalt-nickel alloy on a substrate provided by an embodiment of the present invention has the following excellent properties compared to traditional electroplating methods: ① The coating structure is dense and the conductivity is high; ② The concentration polarization can be reduced and the current density of the cathode can be increased; ③ Oxygen embrittlement can be reduced or eliminated, and the physical and mechanical properties of the coating can be improved; ④ The porosity can be reduced and the quality of the coating can be improved.
[0038] The present invention is further described in detail below through specific examples. Specific embodiments
[0040] This embodiment provides a preparation process for electrodepositing a single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy on a substrate:
[0041] Prepare a plating solution containing nickel and iron ions: use deionized water to prepare 6 L of plating solution containing 160-180 g / L nickel sulfate, 45-55 g / L nickel chloride, 50-60 g / L sodium chloride, 40-60 g / L ferrous sulfate, and 50-60 g / L boric acid.
[0042] Add 50g of activated carbon to the prepared plating solution, and use magnetic stirring to adsorb for more than 4 hours at room temperature, and then use a vacuum filter to remove the residual activated carbon and impurities.
[0043] The cut and polished 304 stainless steel plate and ductile iron plate are placed in an alkaline cleaning solution at 70-80°C, and ultrasonically treated in an ultrasonic machine with an ultrasonic frequency of 30kHz for 20-30 minutes for decontamination and degreasing; then the 304 stainless steel plate and ductile iron plate after alkaline cleaning are placed in deionized water for ultrasonic cleaning for 2-3 minutes to remove the alkaline cleaning solution remaining on the surface; finally, the treated 304 stainless steel plate and ductile iron plate are placed in dilute sulfuric acid with a volume fraction of 10% for ultrasonic treatment for 20-30 seconds to remove the oxide layer on the surface and perform surface activation to obtain a surface-treated cathode plate substrate.
[0044] The 6L plating solution after impurities removal was poured into the electroplating container, and saccharin (C7H5O3NS), sodium dodecyl sulfate (C7H5O3NS) and sodium dodecyl sulfate (C7H5O3NS) were added to the plating solution at concentrations of 5g / L, 0.5g / L and 0.05g / L respectively. 12 H 25 SO4Na) and 1,4-butynediol (C4H6O2) and stir to fully dissolve.
[0045] Place the surface-treated soluble cobalt plate into the plating solution, install the stirring paddle and insert it into the center of the plating tank, adjust the cathode plate material to the relative position of the anode plate, turn on the stirrer and power supply, and perform DC electroplating for 12 hours to increase the cobalt ion concentration in the plating solution and reduce the nickel ion and iron ion concentrations, thus completing the pre-plating test. For the formal electroplating test, the cathode material needs to be replaced with ductile iron, and the anode material needs to be replaced with soluble nickel plate and iron plate. The ductile iron is fixed to the stirring rod with copper wire instead of the stirring paddle. The cathode plate material is adjusted to the center of the plating solution and the distance with the two anode plates is almost the same. The stirring motor is turned on with a current density of 1A / dm 2 , stirring speed of 80-120r / min, bath temperature of 70-80℃, bath pH of 2.0-2.5, under this condition, direct current electroplating for 7 days, so that the cathode material surface is deposited to form a nanocrystalline iron-cobalt-nickel alloy coating with a composition gradient. During the electroplating process, saccharin should be continuously added, and the pH value and metal ion concentration of the bath should be continuously monitored and regulated to finally obtain the desired coating alloy. The thickness of the coating alloy was measured to be 1200-1300um.
[0046] By using ICP to detect the metal ion concentration in the plating solution of the above embodiment, it can be seen that the cobalt ion concentration in the pre-plating solution continues to increase, while the nickel ion and iron ion concentrations continue to decrease. This is to prepare for the formal electroplating and provide cobalt ions for the final gradient alloy. Figure 1 shown.
[0047] By using a scanning electron microscope (SEM) to analyze the surface morphology of the coating alloy in the above embodiment, it can be seen that the alloy surface is smooth and flat, the structure is dense and there is no crack. The test results are as follows: Figure 2 shown.
[0048] Through the use of EDS energy spectrum analysis in a scanning electron microscope (SEM), it can be seen that the coating alloy of the above embodiment presents a composition gradient, and the nickel and iron contents in the alloy gradually increase from the substrate to the alloy surface, while the cobalt content gradually decreases. Figure 3 shown.
[0049] By using an X-ray diffractometer (XRD) to perform micro-area analysis on the cross section of the coating alloy of the above embodiment, it can be seen that the coating alloy of the above embodiment as a whole presents a single-phase structure of FCC, that is, a face-centered cubic structure. The test results are as follows: Figure 4 shown.
[0050] By using a transmission electron microscope (TEM) to analyze the microstructure of the cross section of the coating alloy of the above embodiment, it can be seen that the grain size of the alloy gradually decreases from the matrix to the surface as the alloy composition changes continuously, and the grain size is about 23nm-36nm. The test results are as follows Figure 5 shown.
[0051] By using a nanoindenter to test the cross-sectional hardness of the coating alloy in the above embodiment, it can be seen that the alloy exhibits a gradient hardness characteristic from the substrate to the surface in the thickness direction, that is, the hardness of the alloy increases continuously with the increase of thickness (from the substrate to the surface). The test results are as follows: Figure 6 shown.
Claims
1. The preparation process of electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy has the following characteristics: The initial plating solution is prepared, and then the plating solution is subjected to impurity removal treatment to obtain a plating solution after impurity removal; the concentrations of the components of the initial plating solution are: nickel sulfate (NiSO4.6H2O) 160-180g / L, nickel chloride (NiCl2.6H2O) 45-55g / L, sodium chloride (NaCl) 50-60g / L, ferrous sulfate (FeSO4.6H2O) 40-60g / L, and boric acid (H3BO3) 50-60g / L; Adding the above-mentioned plating solution after impurity removal treatment into the electroplating container, adding anionic surface brightener and anionic wetting agent; First, a pre-plating test is carried out, in which the surface-treated soluble cobalt plate and 304 stainless steel cathode plate material are placed in the plating solution, and direct current electroplating is performed to increase the concentration of cobalt ions in the plating solution and decrease the concentration of nickel ions and iron ions. The pre-plating test is completed to control the concentration of metal ions in the plating solution. Then, the formal electroplating test was carried out. The cathode plate material was changed to ductile iron, and the anode material was changed to soluble nickel plate and iron plate. 2 , stirring speed 80-120r / min, bath temperature 70-80°C, bath pH 2.0-2.5, direct current electroplating for 7 days, so that a nanocrystalline iron-cobalt-nickel alloy coating with a composition gradient is deposited on the surface of the cathode material.
2. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The main steps of removing impurities from the plating solution include: After the plating solution is prepared, add a proper amount of activated carbon, and adsorb for 3-5 hours by magnetic stirring. Then, remove the activated carbon and adsorbed impurities by vacuum filtration to obtain the electroplating solution after impurities removal.
3. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The specific steps include: The impurity-removed plating solution is added into the electroplating container. The main function of adding anionic surface brightener and wetting agent is to make the surface of the cathode coating bright and free of pinholes and pits. The treatment of the soluble iron, cobalt and nickel plates includes: grinding the plates after cutting to remove the surface oxide layer; then ultrasonic cleaning them in alkaline cleaning solution and acid cleaning solution to remove the oil and impurities on the surface, thereby obtaining the treated soluble iron, cobalt and nickel plates; The cathode plate material is treated by firstly performing ultrasonic cleaning in an alkaline cleaning solution to remove oil stains and impurities on the surface of the cathode plate; and then performing ultrasonic treatment in an acid cleaning solution to remove the oxide layer on the surface of the cathode plate and activate the surface to obtain the treated cathode plate material.
4. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 3, characterized in that: The step of processing the cathode plate material comprises: Heat the prepared alkaline cleaning solution to 70-80°C to fully dissolve it, then put the cathode plate into the alkaline cleaning solution for ultrasonic cleaning for 20-30 minutes, put the alkaline-washed cathode plate into deionized water for ultrasonic cleaning for 2-3 minutes, and then put the cathode plate into the acid cleaning solution for ultrasonic cleaning for 20-30 seconds to complete the surface treatment of the cathode plate; The concentrations of the components of the alkaline washing solution and the acid washing solution are as follows: alkaline washing solution: sodium hydroxide (NaOH) 80g / L, sodium carbonate (Na2CO3) 50g / L, sodium silicate (Na2SiO3) 30g / L, sodium phosphate (Na3PO4) 10g / L; acid washing solution: dilute sulfuric acid solution with a volume fraction of 10%.
5. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The electroplating steps include: Put the surface treated soluble nickel plates, cobalt plates and iron plates into the electroplating container. When there is only one anode plate, the single anode deposition method is adopted, and the anode is hung and fixed on the surface of any side in the electroplating container, and the cathode plate material is hung and fixed on the inner surface of the plating tank opposite to it for electroplating; when there are two anode plates, the rotating cathode deposition method is adopted, and the two anodes are respectively fixed and hung on the inner surfaces of two opposite plating tanks, and the cathode plate material is fixed on the stirring rod with copper wire instead of the stirring paddle, and the cathode plate material is adjusted to the center of the plating solution and the distance with the two anode plates is almost the same, and the stirring motor is turned on for electroplating.
6. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The thickness of the iron-cobalt-nickel alloy coating is 1200-1300um.
7. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: There are two types of anionic surface brighteners, namely saccharin (C7H5O3NS) and 1,4-butynediol (C4H6O2); the anionic wetting agent is sodium dodecyl sulfate (C 12 H 25 SO4Na).
8. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The cathode plate material size is 10cm×10cm.
9. The process for preparing the electrodeposited single-phase composition gradient nanocrystalline iron-cobalt-nickel alloy according to claim 1, characterized in that: The anode material of the pre-plating test is a soluble cobalt plate, and the initial plating solution is a nickel-iron solution. Therefore, a 12-hour pre-plating test can effectively increase the concentration of cobalt ions in the plating solution and consume the concentrations of nickel ions and iron ions in the plating solution. The anode materials of the formal electroplating test are nickel plates and iron plates. Therefore, during the electroplating process, the nickel ions and iron ions in the plating solution will be continuously replenished and increased, while the cobalt ions will be continuously consumed due to lack of replenishment, which will also be reflected in the final coating composition distribution, and a nanocrystalline iron-cobalt-nickel alloy coating with a composition gradient will be obtained. The composition gradient characteristics of the coating alloy in the thickness direction will cause the alloy to produce a structural gradient and a performance gradient, which is reflected in the fact that the grain size and hardness of the alloy along the thickness direction of the coating both show gradient characteristics.
